2021
DOI: 10.1038/s41388-021-01665-0
|View full text |Cite
|
Sign up to set email alerts
|

Classification of node-positive melanomas into prognostic subgroups using keratin, immune, and melanogenesis expression patterns

Abstract: Cutaneous melanoma tumors are heterogeneous and show diverse responses to treatment. Identification of robust molecular biomarkers for classifying melanoma tumors into clinically distinct and homogenous subtypes is crucial for improving the diagnosis and treatment of the disease. In this study, we present a classification of melanoma tumors into four subtypes with different survival profiles based on three distinct gene expression signatures: keratin, immune, and melanogenesis. The melanogenesis expression pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 57 publications
2
12
0
Order By: Relevance
“…This is consistent with the GO and KEGG enrichment analysis of SERP1 in patients with SKCM in our study. Additionally, the predicted genes used in the study to validate the keratin group, including IVL and SPRR1B [ 28 ], are consistent with the hub genes of DEGs from cytoHubba and MCODE in our analysis. Thus, keratinization, epidermis development, and cornification related to SERP1 are likely to play an important role in the tumorigenesis and prognosis of SKCM.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…This is consistent with the GO and KEGG enrichment analysis of SERP1 in patients with SKCM in our study. Additionally, the predicted genes used in the study to validate the keratin group, including IVL and SPRR1B [ 28 ], are consistent with the hub genes of DEGs from cytoHubba and MCODE in our analysis. Thus, keratinization, epidermis development, and cornification related to SERP1 are likely to play an important role in the tumorigenesis and prognosis of SKCM.…”
Section: Discussionsupporting
confidence: 72%
“…Early stage SKCM has a better prognosis after surgical resection; however, SKCM tends to subcutaneously metastasize to regional lymph nodes and distant organs, which complicated treatment for advanced stages [ 27 ]. Netanely et al [ 28 ] divided melanoma tumors into four subtypes according to different gene expression signatures and validated the classification. They found that the keratin group has the lowest survival rate, significantly higher Breslow depths, and higher pathologic T values.…”
Section: Discussionmentioning
confidence: 99%
“…This state has translational importance, since clinical data has correlated differentiated melanocytic identity with worse clinical outcomes [16][17][18][19] . Acquisition of a differentiated melanocytic cell identity has been associated with metastatic seeding and evasion to targeted therapy in patients, highlighting the need to uncover vulnerabilities in this cell state 19,20 . Dissecting the mechanisms driving this state requires tractable genetic models that recapitulate human melanoma phenotypic heterogeneity while preserving an immunocompetent TME.…”
mentioning
confidence: 99%
“…In addition, TIGIT, which is a T-cell immune receptor with Ig and ITIM domains ( 31 ) and was upregulated in the high-immunity, has been recently identified as an attractive cancer immunotherapy target, because of its key role in interactions between the cells within the tumor microenvironment. The down-regulated genes were enriched in cornification, epidermis development, and keratin-related process ( Figure 2G ), all of which are associated with forming the outermost skin barrier ( 32 ). For example, human tissue kallikreins 7 (hKLK7) takes part in skin desquamation, which has been involved in keratinocyte cell shedding to catalyze the degradation of intercellular cohesive structures at the skin surface ( 33 ).…”
Section: Resultsmentioning
confidence: 99%